Online customer experience in e-retailing - Iucolano, Donna M. (Henry Stewart Talks, 2014)
Online customer experience defined, Current size and projected growth of digital commerce, Changing customer expectations, 8 factors contributing to great online customer experience, 10 implications for retailers (reasons for striving to deliver a great customer experience)